Termopotássio na cultura da cana-de-açúcar - Assis, Rafael Tadeu de (2018)
The sugarcane crop is highly demanding in potassium, a nutrient that needs to be largely imported. Other alternative sources of potassium can deliver it, but their results in sugar cane are still little studied. Thus, the objective of this study was to evaluate technological attributes of sugarcane, productivity, chemical attributes of the leaf and soil by the application of thermopotassium in the furrow at the sugarcane planting. This field experiment was carried out in three commercial areas of sugarcane production in the states of Goiás and São Paulo. Evaluations of soil and plant occurred approximately eight months after the installation of the experiments. The variables that showed significant differences (p < 0.05) in the plants studied showed favorable results to the cultivation of sugarcane with the application of TK47 thermopotassium. The application of lower doses of K2O as thermopotassium presented results similar or superior to 400 kg ha-1 of K2O applied as KCl. The application of TK47 thermopotassium is an excellent alternative for the supply of K and other nutrients (Ca, Mg, Si) for sugarcane in the first year of crop production.